Electrum Coinage of the Scythians - Butkevych, Ivan (KOINON: The International Journal of Classical Numismatic Studies, 2023)
The era of electrum coinage is among the most popular topics for research. Indeed, it is difficult to imagine any other period in the history of coinage so plentiful for all kinds of assumptions and hypotheses. However, in spite of so much attention from researchers, we can emphasize that the scope of our reliable knowledge about these coins is much smaller than the area of the unknown. One of the most mysterious pages of the story are electrum coins of a special type, the known findings of which come from the region of the ancient settlement Borysthenes, located at the mouth of the Dnieper-Bug estuary (Figure 1). In this article, I will discuss these coins in connection with their historical and cultural background, arguing that they were struck for the Scythian elites as prestige issues and brought to Berezan Island when the Scythians left Lydian territory. Furthermore, I argue that some of the reverse designs likely derive from the Median cuneiform logogram meaning ‘King,’ or ‘Chief,’ referring of course to the leader of the Scythians.